Information Needs, Accessibility and Utilization of Library Information Resources as Facilitators of Teaching Effectiveness of Lecturers in Library and Information Science Schools in Nigeria - Onifade, G. O.; Popoola, S. O. (MiddleBelt Journal of Library and Information Science, 2015)
Despite various efforts at improving the quality and learning outcome in library schools at the university level in Nigeria, many students are still performing below expectation. This has been traced to low level of teaching effectiveness of lecturers. This paper, therefore, examined the contributions of information needs, accessibility and utilization of library information resources to teaching effectiveness of lecturers in library and information science schools in Nigeria. Total enumeration technique coupled with a questionnaire was used to collect data on a population size 265 lecturers in 24 universities in Nigerian, out of which 200 responded given a response rate of 76%. The study found that information needs, accessibility and utilization of library information resources had significant collinear relationship with teaching effectiveness of the respondents. In addition, information needs, accessibility and utilization of library information resources significantly facilitated teaching effectiveness of the respondents. More so, each of the independent variables: information needs, accessibility and utilization of library information resources has relative contribution and significantly facilitates teaching effectiveness of the respondents. The paper concluded that more focus needs to be on the practice of teaching at the university level. Consequently, it is recommended that the university authorities should consider information needs, accessibility and utilization of LIRs for teaching effectiveness of lecturers.